2018
DOI: 10.1186/s12913-018-2923-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding perceived availability and importance of tobacco control interventions to inform European adoption of a UK economic model: a cross-sectional study

Abstract: BackgroundThe evidence on the extent to which stakeholders in different European countries agree with availability and importance of tobacco-control interventions is limited. This study assessed and compared stakeholders’ views from five European countries and compared the perceived ranking of interventions with evidence-based ranking using cost-effectiveness data.MethodsAn interview survey (face-to-face, by phone or Skype) was conducted between April and July 2014 with five categories of stakeholders - decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The scoping review revealed that numerous AI solutions exist, particularly in the era of “Big data” and are continuing their development ( 42 , 47 ), however, choosing the best approach seems to be entirely dependent on the domain and the expertise of the people involved in this domain. Unlike other applied fields, HTA has several components—clinical, economical, ethical, legal, and socio-cultural where as recently as 2018 the need for standardized good practices was identified ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoping review revealed that numerous AI solutions exist, particularly in the era of “Big data” and are continuing their development ( 42 , 47 ), however, choosing the best approach seems to be entirely dependent on the domain and the expertise of the people involved in this domain. Unlike other applied fields, HTA has several components—clinical, economical, ethical, legal, and socio-cultural where as recently as 2018 the need for standardized good practices was identified ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The works of Basch (36) regarded the most impactful factors as being cultural, economic, social, institutional factors, as well as affordability, cost-effectiveness, and satisfying public demands. All other articles within this group are mostly concerned by the barriers in front the health technology assessment of new health technologies and their usage in the East European Countries jurisdiction (37)(38)(39)(40)(41)(42)(43)(44)(45). The barriers pointed out in the articles focused mainly on the methodological quality of documentation, differences in epidemiology and demographics, knowledge and differences in decision making criteria, differences in the organization of health care services delivery (46).…”
Section: Barriers Discussed In the Literaturementioning
confidence: 99%